Predictive Factors of Response in HER2-Positive Breast Cancer Treated by Neoadjuvant Therapy. (29th April 2013) - Guiu, S.; Mouret Reynier, M. A.; Toure, M.; Coudert, B.
Abstract : Since 2005, major progresses have been made in the neoadjuvant treatment of HER2-positive breast cancer. Trastuzumab introduction associated with chemotherapy has been the first major step leading to the improvement of the complete pathological response rate and, like in the adjuvant studies, better survivals. Dual HER2 blockade has been the next step and trastuzumab is associated now with other anti-HER2 therapies like lapatinib or pertuzumab, the latter being much more easy to use in combination with chemotherapy. Additional knowledge is necessary to better define within the HER2 tumor subgroup which patients could benefit more from targeted therapies. Different biomarkers have been studied to predict the response after anti-HER2 neoadjuvant therapies but until now none has been validated.